Spatial Planning in Cracow - An Evaluation of the State of and Current Activities in the Field of Spatial Planning in the Light of a Survey - Brańka, Patrycja; Hołuj, Artur (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
Given the numerous actors involved, spatial planning in metropolitan areas is a complex and sophisticated process. Spatial as well as ecological conflicts arise from the different ways of perceiving and understanding space and its resources. As one of Poland’s largest cities, Cracow’s specific role in this domain is illustrated. The main aim of the survey, which was conducted among local authorities and inhabitants alike, shows the opinions of the two groups on the role of spatial planning, its impact on local development, and the quality of spatial policy in Cracow. Another objective of the study was to identify the involvement of the inhabitants of Cracow in the process of spatial planning.